Monopolizing mobilities: The data politics of ride-hailing platforms in US cities. (December 2020) - Monahan, Torin
Highlights: Transportation network companies (TNCs) resist sharing data with city transportation departments. TNC data are essential for diagnosing city needs and providing services for the public good. Restricted data sharing entrenches platform practices and logics in cities. An alternative "data commons" approach could support inclusive, equitable, and safe mobilities in cities. Abstract: Smart-urbanism discourses frequently invoke the transformative potential of data to solve city problems, but data are neither neutral nor are they readily shared in the pursuit of common goals. Drawing upon a two-year study of large-scale digital platforms in US cities, this paper investigates conflicts over data sharing between city transportation departments and ride-hailing companies such as Uber and Lyft. By maintaining data monopolies, platform companies obfuscate the detrimental impacts of their services (e.g., increased congestion and pollution, dangers to cyclists and pedestrians) and interfere with city transportation planners' tasks of diagnosing city needs and providing services for the public good. Ride-hailing companies' resistance to data sharing serves the strategic goals of prolonging monopoly status and slowing regulation for maximum capital extraction, but I argue that it also performs a more insidious function of entrenching platform practices and logics, making alternatives difficult to imagine or implement. Against this backdrop, I explore the notion of a "data commons" approach to transportation management.